BK Pola 17 dalam Manajemen Bimbingan dan Konseling di SMP Jati Agung Taman Sidoarjo - Fathul Fauzi (rogram Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2019)
The research conducted in reviewing BK Pola 17 in Guidance and Counseling Management in SMP Jati Agung Sidoarjo with the aim to find out how to implement BK Pattern 17, how to implement Guidance and Counseling management and how to implement BK Pola 17 in Guidance and Counseling management in SMP Jati Agung Sidoarjo?.This research uses qualitative research and is carried out with the method of observation, interview, and view documentary data. Then the new data is analyzed using three steps namely data reduction, data display, verification and conclusions in order to get the results of the actual and in-depth data analysis in accordance with the research topic. The results showed that: BK Pola 17 in SMP Jati Agung Sidoarjo was in accordance with Minister of Education and Culture Decree No. 025 / O / 1995, which explains the terms of Guidance and Counseling, namely assistance services for students both individually and in groups, to be able to be independent and develop optimally in the field of personal, social, learning, and career guidance through various types of services and activities supporters based on applicable norms. But there is one service that has not been implemented, namely group counseling services. Guidance and Counseling Management in SMP Jati Agung Sidoarjo is generally good, but for the management of time and counseling and facilities in SMP Jati Agung Sidoarjo is still lacking so the planned program has not been maximized. BK Pola 17 in the Guidance and Counseling management in SMP Jati Agung Sidoarjo, the implementation is in accordance with the rules, namely for students' self-development has been programmed using the Melapendis reference book (Student Self-Development Services Media).